2022
DOI: 10.3389/fcvm.2022.816404
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Right Ventricular Dysfunction on Outcomes of Left Ventricular Non-compaction Cardiomyopathy

Abstract: BackgroundVarious adverse outcomes such as mortality and rehospitalization are associated with left ventricular non-compaction (LVNC). Due to data limitations, prospective risk assessment for LVNC remains challenging. This study aimed to investigate the influence of right ventricular (RV) dysfunction on the clinical outcomes of patients with LVNC through accurate and comprehensive measurements of RV function.Methods and ResultsOverall, 117 patients with LVNC (47.6 ± 18.3 years, 34.2% male) were enrolled, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…47 These excess corticosteroids may play an important role in pathways involved in endothelial dysfunction, which has been proposed to cause relentless hypoxia in the cardiovascular microcirculation and consequently myocardial injury followed by increased myocardial fibrosis. 48,49 The association between the two-corticosteroid precursor-based CMD score and the IHF outcome in our study further suggests the notion of a vital role of corticosteroids in the pathogenesis of IHF. Nonetheless, further studies are necessary to confirm these findings and their pathophysiologic relevance.…”
Section: Discussionsupporting
confidence: 69%
“…47 These excess corticosteroids may play an important role in pathways involved in endothelial dysfunction, which has been proposed to cause relentless hypoxia in the cardiovascular microcirculation and consequently myocardial injury followed by increased myocardial fibrosis. 48,49 The association between the two-corticosteroid precursor-based CMD score and the IHF outcome in our study further suggests the notion of a vital role of corticosteroids in the pathogenesis of IHF. Nonetheless, further studies are necessary to confirm these findings and their pathophysiologic relevance.…”
Section: Discussionsupporting
confidence: 69%
“…However, our study did not show volumetric differences, which might be due to the smaller patient population. Moreover, a novel study of 117 noncompacted participants using 2D STE demonstrated that decreased conventional parameters for right ventricular function (tricuspid annular systolic excursions, tricuspid S′ velocity, and RV fractional area change and reduced right ventricular strain values) were all independent predictors of mortality, regardless of the left ventricular EF [21] , [22] .…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the abovementioned correspondences were not observable in the DCM group. It must be emphasized that RV involvement in LVNC has a worse prognosis based on literature data [ 32 , 33 ]. Regarding our results, RV trabeculation might have an impact on the deterioration of RV strains.…”
Section: Discussionmentioning
confidence: 99%